1996
DOI: 10.1021/bi9614702
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Studies of the Catalytic and a Second Site in Fumarase C from Escherichia coli,

Abstract: Fumarase C catalyzes the stereospecific interconversion of fumarate to L-malate as part of the metabolic citric acid or Kreb's cycle. The recent three-dimensional structure of fumarase C from Escherichia coli has identified a binding site for anions which is generated by side chains from three of the four subunits within the tetramer (Weaver et al., 1995). These same side chains are found in the three most highly conserved regions within the class II fumarase superfamily. The site was initially characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(151 citation statements)
references
References 35 publications
(58 reference statements)
8
138
0
Order By: Relevance
“…4,8,23,26 Similar roles have been proposed for the equivalent histidine/ glutamate residues in ASL/δ2-crystallin 8,27-29 and fumarase C. 4,30 Mutation of H171 with a variety of substitutions (e.g. A, L, E, Q, R) in bs-ADL has highlighted the importance of this residue in catalysis, as residual activity was only detected in the H171R mutant, which was found to be 10 5 -fold less active than the wild-type enzyme.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…4,8,23,26 Similar roles have been proposed for the equivalent histidine/ glutamate residues in ASL/δ2-crystallin 8,27-29 and fumarase C. 4,30 Mutation of H171 with a variety of substitutions (e.g. A, L, E, Q, R) in bs-ADL has highlighted the importance of this residue in catalysis, as residual activity was only detected in the H171R mutant, which was found to be 10 5 -fold less active than the wild-type enzyme.…”
Section: Resultsmentioning
confidence: 61%
“…This residue is strictly conserved across the superfamily and has been suggested to play a role in stabilizing the aci-carboxylate intermediate in several of the superfamily members. 12,13,30 This proposal is supported by mutagenesis experiments in E. coli L-aspartase 13 and dδc2 (M. T., unpublished work), and by the dδc1-sulfate complex, which demonstrated that closure of the C3 loop over the active site enabled the N Îś atom of the equivalent lysine residue to interact with the sulfate ion. 33 However, in the H171A-ADS complex K301 is not in a position to interact with the δ-carboxylate group of the substrate, on which the negative charges accumulate in the aci-carboxylate intermediate.…”
Section: Stabilization Of the Aci-carboxylate Intermediatementioning
confidence: 92%
“…Both homologs form a stable homotetramer containing four active sites, and every active site is composed of residues from three enzyme subunits. Each dumbbell-shaped subunit within the tetramer contains three domains: an N-terminal domain, a central domain, and a C-terminal domain (8)(9)(10). The N-and C-terminal domains are predominantly Îą-helical and linked by the central domain that consists of five tightly packed helices.…”
mentioning
confidence: 99%
“…E. coli fumarase is unrelated to CM in sequence or function but, like CM, is largely ␣-helical (24). To evaluate in a broad and unbiased manner the ability of foreign protein fragments to substitute regions of CM, fumarase was recombined with mMjCM by using protein NRR.…”
Section: Recombination With An Unrelated Protein Results In Active Chmentioning
confidence: 99%